Impact of the Pandemic on Sexual and Reproductive Health Services in Low Income Countries with Reference to Nepal (Patan Pragya, 2020)
Access to reproductive health services saves women for safe sex, safe pregnancy and child birth. This paper intends to analyze the impact of pandemic on reproductive health services during one decade 1920-2020 B.S. To achieve the above mentioned objective, descriptive method is used. Data are collected from secondary sources and major biggest pandemic of one hundred years which have larger impact on public health including reproductive health and large scale of mortality. The history of pandemic shows that service delivery of reproductive health to women was seriously affected during pandemic period. There was difficult to achieve basic health facility to pregnant women during pandemic period, they also face problems to achieve reproductive health services. The influenza   affects to the pregnant women. They were severely ill during their pregnancy. There was a negative impression with health providers and pregnant women at health centre at the time of providing sexual and reproductive health services during the Ebola virus. The Zika virus effects on women's sexual and reproductive rights. The reproductive health services became at more serious cases at the time of HIV/AIDS pandemic. Pregnant women, infants and young children had serious impact of H1N1 virus. Women are facing problems to get reproductive health services like access of family planning, abortion care and other infectious diseases during Covid-19 periods. These problems also increased risk to unwanted pregnancy, risk of unsafe abortion and risk of STDs to the women. Women were facing lacking of sexual and reproductive health services due to the lockdown, physical distance, travel restrictions and economic slowdown during covid-19 pandemic.